Evaluasi Kinerja Pemerintah Desa Dalam Penyelenggaraan Program Desa Mandiri Studi Kasus Desa Tumori Kecamatan Gunungsitoli Barat - Deven Awaizawato Zebua; Suka'aro Waruwu; Eliagus Telaumbanua; Delipiter Lase (Jurnal Publikasi Manajemen Informatika, 2024)
This research work is expected to provide a deeper insight into the factors related to the performance of the village government in implementing the Independent Village program, as well as providing recommendations for the improvement and development of the program in the future. The researcher determined the type of research used, namely the qualitative method where this method emphasizes more on observing phenomena and examining the substance of the meaning of the phenomenon and is greatly influenced by the power of words and sentences or often said to be in the form of statements or sentences. The results of the study are: First, the evaluation of the performance of the Tumori Village government in general has been going well, but there are still several sub-parameters that have not reached the maximum limit. Second, in the process of implementing the Independent Village Program, Tumori Village strives to support human resource development, natural resource management, management of local village potential and improving the community's economy. Third, the efforts made in implementing the Independent Village are by implementing the PKTD (Village Cash for Work) program where this program involves the entire community in village development activities or projects in order to support the economy, provide jobs, and improve the welfare of the entire community.